A cost‐effectiveness analysis of optimal care for diabetic foot ulcers in Australia. Issue 4 (4th August 2016) - Cheng, Qinglu; Lazzarini, Peter A; Gibb, Michelle; Derhy, Patrick H; Kinnear, Ewan M; Burn, Edward; Graves, Nicholas; Norman, Rosana E
Abstract: In addition to affecting quality of life, diabetic foot ulcers (DFUs) impose an economic burden on both patients and the health system. This study developed a Markov model to analyse the cost‐effectiveness of implementing optimal care in comparison with the continuation of usual care for diabetic patients at high risk of DFUs in the Australian setting. The model results demonstrated overall 5‐year cost savings (AUD 9100·11 for those aged 35–54, 9391·60 for those aged 55–74 and 12 394·97 for those aged 75 or older) and improved health benefits measured in quality‐adjusted life years (QALYs) (0·13 QALYs, 0·13 QALYs and 0·16 QALYs, respectively) for high‐risk patients receiving optimal care for DFUs compared with usual care. Total cost savings for Australia were estimated at AUD 2·7 billion over 5 years. Probabilistic sensitivity analysis showed that optimal care always had a higher probability of costing less and generating more health benefits. This study provides important evidence to inform Australian policy decisions on the efficient use of health resources and supports the implementation of evidence‐based optimal care in Australia. Furthermore, this information is of great importance for comparable developed countries that could reap similar benefits from investing in these well‐known evidence‐based strategies.